Risk Factors Associated with 28-Day Mortality of COVID-19 Patients at RSUP Dr. M. Djamil Padang - Lusi Agustini Arda; Oea Khairsyaf; Russilawati Russilawati; Tuti Handayani (Jurnal Respirologi Indonesia, 2023)
Background: The COVID-19 mortality rate varies widely around the world. The COVID-19 death rate in Indonesia is currently relatively higher than the world average and is the highest in Southeast Asia. Data regarding risk factors of COVID-19 mortality in Indonesia, particularly West Sumatra, are still scarce. This study aims to determine the risk factors associated with the 28-day mortality of COVID-19 patients at RSUP Dr. M. Djamil Padang.Methods: This was an observational analytic study with a retrospective cohort approach on confirmed COVID-19 inpatients who were treated at RSUP Dr. M. Djamil Padang between January 1 and March 31, 2021. A bivariate analysis using Chi square was calculated to see the correlation between clinical severity, and routine blood values, markers of inflammation, liver function, kidney function, blood gas analysis, the RALE score and comorbidities with a 28-day mortality outcome. To assess the dominant risk factors, multivariate analysis was performed using logistic regression.Results: From 245 samples, patients aged >50 years and women were the most treated group of patients. Bivariate analysis obtained the following critical clinical grade factors: Hb <10 g/dl, leukocyte level >10.0x103/mm3, monocyte level 8.0%, procalcitonin level >0.5 ng/ml, interleukin-6 level >7 pg/ml, ferritin >159/ml, D-Dimer level >500 ng/dl, SGOT level >38 μ/l, urea >50 mg/dl, creatinine >1.3 mg/dl, PO2 <80 mmHg, SO2 ≤90%, PO2/FiO2 ≤300 mmHg, high RALE score, comorbid of chronic renal failure, hypertension, type II DM; and comorbidities >1 were associated with 28 days of death. Multivariate analysis identified critical clinical severity as the dominant risk factor (OR=8.47; 95% CI=2.55–28.14; P<0.001).Conclusion: Critical clinical severity was the dominant risk factor associated with the 28-day mortality of COVID-19 patients at RSUP Dr. M. Djamil.